Efficacy of Aceclofenac and Naproxen in Patients with Low Back Pain at Birat Medical College and Teaching Hospital - Gupta, Prem Kumar; Kafle, Gokul; Roy, R K; Gupta, Prashant; Dewasy, Bijoylakshmi (Journal of Nobel Medical College, 2025)
Background: Low back pain is a common global problem with a high incidence in Nepal and is a cause of disability. Non-Steroidal Anti-Inflammatory Drugs are the first-line option for managing both acute and chronic low back pain. This study aims to compare the efficacy and safety of Aceclofenac and Naproxen for acute low back pain due to the limited comparative data locally.Materials and Methods: This prospective, observational study at Birat Medical College enrolled 88 acute low back pain patients; categorized in two groups by simple random sampling, receive either Aceclofenac 100 mg twice daily or Naproxen 500 mg twice daily. Efficacy was assessed by measuring pain intensity with a Visual Analog Scale at baseline and one week after treatment, and monitoring adverse effects via a self-report checklist. Statistical significance was set at p < 0.05.Results: Baseline mean Visual Analog Scale pain scores were similar for both groups. By Day 7, mean Visual Analog Scale for Aceclofenac (3.0±0.96) was significantly lower in contrast to Naproxen (5.0±1.00), a difference was significant (p < 0.001) in paired t-test. Aceclofenac also had a superior safety profile with absence of side-effects, while Naproxen showed mild gastrointestinal problems in three patients. Our study also indicated significant associations for acute low back pain with variables such as age, gender, occupational status, and heavy physical work.Conclusion: Aceclofenac demonstrated superior pain relief and a better safety profile than Naproxen for acute low back pain. It is thus a preferable therapeutic option for use in similar clinical settings.